The impact of ethics on growth and development: environmental economy versus ecological economy? - Jiménez Sotelo, Renzo A. (2018)
In this paper, it is argued that many of the prescriptions of economic policy to promote growth and achieve development tend to be divergent because they use different moral assessment systems at heart. This happens because the economics cannot define welfare without resorting to any particular ethic. The different ethics chosen explains the relationship between free market speech and the environmental economics and the evolution of the critique made by the ecological economics. This in turn reveals the differences between the concepts of growth and development: all profit needs consumption expenditure, but all welfare does not. Even, paradoxically,promoting indicators of sustained growth should not be anecessary condition for achieving sustainable development.